DENTAL CARIES IN PREGNANT WOMEN WHO VISITED POSYANDU OF SEVERAL PUBLIC HEALTH CENTERS IN JEMBER - Ristya Widi Endah Yani; Hestieyonini Hadnyanawati; Kiswaluyo Kiswaluyo (UPT Penerbitan Universitas Jember)
Pregnancy is a unique period for a woman’s life,which there is physical and physiological changesincluding the oral cavity [1], [2].The main salivary changes in pregnancy are salivarate change, composition, pH, and hormone levels[3]. During pregnancy, pH of saliva and gingival fluidbecome more acidic [4]. Increased acid production inthe oral cavity when accompanied by a lackawareness of pregnant women in maintaining thecleanliness of the oral cavity will expedite theemergence of caries. Based on data of RiskesdasMinistry of Health in 2013, the prevalence of cariesin Indonesia was 53.2%, therefore the maintenanceof the teeth of pregnant women should be takeninto account and improved [5].Caries etiologies are multi factorial. They are hosts,saliva, microorganisms and time [6]. Based on thebackground above, author wanted to know dentalcaries in pregnant women who visit Posyandu ofseveral public health centers in Jember.